Evolution stages of the spatial urban development - Стеблецька, Ю. (Київський національний університет імені Тараса Шевченка, 2016)
The factors influencing the change of urban space were considered. Key stages of urban geohistory were emphasized and in accordance with that the main historical types of cities were grouped. Each evolution stage of the spatial urban development was in detail analyzed. The main features, processes, and superior system of settlement for all historical types of cities were defined. Outstanding characteristics of all historical types of cities of all ages were determined and described. A table for features of historical types of cities on key indicators was designed. A decisive influence of economic systems on urban form and its social geography was defined. The influence of the transition of settlements from the early preindustrial economy to the classical industrial city through a capitalist economy, and later to modern approaches and trends in the so-called theory of “post-industrial” city through research of urban geohistory was traced. The way of decay of urban planning of preindustrial age from the rigidly regulated by the state, however well-ordered and well-thought-out planning on the basis of an orthogonal grid in ancient cities, to the spontaneous and disordered development in the Middle Ages, when the core of the city was the fortress and monastery, was studied. Typicality of the cities of the industrial age of the return from the uncontrolled growth, when the decisive role was played by differentiated rents for land in the early models of the industrial city, to the functional zoning in the age of modernism was defined. Urban planning in the post-industrial age in terms of the traditional city through the global processes of urbanization, which create new socio-spatial forms of settlements (metropolitan region, multicentered metropolitan regions) were described. The impact of globalization on the urban space and on creation of new forms of urban settlements was considered. Social and economic features that indicate the development of postmodern metropolis were considered.

Розглянуто фактори, що впливають на зміни міського простору. Виділено ключові етапи геоісторії міст та відповідно до цього згруповані основні історичні типи міст. Детально проаналізовано кожну стадію еволюції просторового розвитку міст. Визначено основні характерні ознаки міського простору, процеси та переважаюча система розселення для всіх історичних типів міст. Розроблено таблицю характеристики історичних типів міст за основними індикаторами: домінуюча планувальна структура (модель), основні містобудівні “одиниці” та поняття, режим планування розвитку міст.
Стадії еволюції просторового розвитку міста
Paul Knox, Steven Pinch. Urban social geography: an introduction. 2010. Peter Hall. Cities in Civilization. – NY,1998. Peter Hall. Cities of Tomorrow: An Intellectual History of Urban Planning and Design in the Twentieth Century. – Oxford, 2002. Spiro Kostof. The City Shaped: Urban Patterns and Meanings Through History. – London, 1999. Spiro Kostof. The City Assembled: The Elements of Urban Form Through History. – Boston, Toronto, London, 1992. Joseph Rykwert. The Seduction of Place: The History and Future of the City. – NY, 2002. Vozniak Т. Narodzhennia ta heneza idei “idealnoho mista” [Birth and genesis of the idea of “ideal city”]. // Fenomen mista Available at: http://www.ji.lviv.ua/ji-library/Vozniak/misto/narodzhennja_ta_geneza.htm Dronova O. L. Heourbanistyka: navch. Posib. [Geourbanistics: tutorial] / O. L. Dronova. – K., 2014. Herasymchuk Z.V., Nishchyk T.O. Prostorovyi rozvytok mista. Monohrafiia [The spatial development of the city. Monograph]. – Lutsk, 2011. 10. Frolova E.D. Issledovaniya i publikatsii po istorii antichnogo mira [Research and publications on the history of the ancient world] // Mnemon. – 2005 – №4. Available at: http://centant.spbu.ru/centrum/publik/kafsbor/mnemon05.htm. Pertsik E.N. Geografiya gorodov (geourbanistika): Uchebn. posobie dlya geogr. spets. Vuzov [Urban geography: tutorial for geographical high schools]. – 1991. Pleshkanovskaya A.M., Savchenko E.D. Goroda i epohi [Cities and ages]. – K., 2011. Edward Soja. Postmetropolys. Krytycheskye yssledovanyia horodov y rehyonov [Postmetropolis. Critical studies of cities and regions]. – 2003. – № 6. Available at: http://www.ruthenia.ru/logos/number/40/09.pdf Chepelyk O. V. Vzaiemodiia arkhitekturnykh prostoriv, suchasnoho mystetstva ta novitnikh tekhnolohii [Interaction of architectural spaces, contemporary art and new technologies] -, 2009.
Keywords: доіндустріальне місто; стародавнє місто; середньовічне місто; “ідеальне місто”; індустріальне місто; місто модернізму; постіндустріальне місто; preindustrial city; ancient city; medieval city; “ideal city”; industrial city; city of modernism; post-industrial city